2014
DOI: 10.1371/journal.pone.0098685
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity and Safety of a Genetically Modified Influenza Virus Vaccine

Abstract: Recombinant influenza viruses are promising viral platforms to be used as antigen delivery vectors. To this aim, one of the most promising approaches consists of generating recombinant viruses harboring partially truncated neuraminidase (NA) segments. To date, all studies have pointed to safety and usefulness of this viral platform. However, some aspects of the inflammatory and immune responses triggered by those recombinant viruses and their safety to immunocompromised hosts remained to be elucidated. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Our previous study showed that the IAV load in lungs peaked at about the fourth day after infection and that IAV was cleared by day 10 (Barbosa et al, 2014 ). Therefore, our data strongly suggested a link between high viral replication and increased susceptibility to Cg during acute influenza infections.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Our previous study showed that the IAV load in lungs peaked at about the fourth day after infection and that IAV was cleared by day 10 (Barbosa et al, 2014 ). Therefore, our data strongly suggested a link between high viral replication and increased susceptibility to Cg during acute influenza infections.…”
Section: Resultsmentioning
confidence: 94%
“…Our preliminary findings showed that a deleterious effect of co-infection was evident only in mice exposed to IAV 3 days before inoculation with Cg. Notably, day 3 of IAV infection coincides with high levels of virus in infected lungs (Ayala et al, 2011 ; Pan et al, 2013 ; Barbosa et al, 2014 ). The importance of active viral multiplication in this predisposition to severe pulmonary cryptococcal disease was demonstrated by treatment with the antiviral oseltamivir, which delayed mortality of mice co-infected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intranasal delivery of a peptide vaccine for the major cause of respiratory disease in young children, the respiratory syncytial virus, has shown promise in animal models, but these have yet to be tested in humans [47]. Similarly, intranasal immunisation of mice with genetically modified, recombinant influenza virus was shown to drive protective humoral and cellular antiviral immune responses and was effective even in immunocompromised host animals [48]. Pulmonary delivery has proved more successful for human disease control for measles, although here the immune responses are dependent on the formulation, with dry powder eliciting lower immunity than intramuscular injections (in an animal model) and the age of the population, since clinical trials using nebulised liquid vaccine was shown to be less effective in younger children [49]…”
Section: The Need For Pulmonary Vaccine Deliverymentioning
confidence: 99%